2013
DOI: 10.1111/acel.12088
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction in humans inhibits the PI3K/AKT pathway and induces a younger transcription profile

Abstract: Summary Caloric restriction (CR) and down-regulation of the insulin/IGF pathway are the most robust interventions known to increase longevity in lower organisms. However, little is known about the molecular adaptations induced by CR in humans. Here we report that long-term CR in humans inhibits the IGF-1/insulin pathway in skeletal muscle, a key metabolic tissue. We also demonstrate that CR-induced dramatic changes of the skeletal muscle transcriptional profile that resemble those of younger individuals. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(169 citation statements)
references
References 25 publications
11
154
1
3
Order By: Relevance
“…Although Akt is known to play important roles in the signaling pathways of several cellular functions including nutrient metabolism, cell growth, apoptosis, and survival (Song et al 2005), none of the seven Akt1 single-nucleotide polymorphisms (SNPs) studied were significantly associated with longevity in humans (Nygaard et al 2013). The difference in our results and those of Nojima et al (2013) and Mercken et al (2013) could be due to different experimental organisms with greatly differing genetic architecture and/or due to specific effects of curcumin. Contrary to earlier findings of reduced CG9510 (Heinrichsen et al 2013) and AKHR (Iijima et al 2009) activity leading to increased triglyceride levels, flies from F C had significantly lower triglycerides (Fig.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Although Akt is known to play important roles in the signaling pathways of several cellular functions including nutrient metabolism, cell growth, apoptosis, and survival (Song et al 2005), none of the seven Akt1 single-nucleotide polymorphisms (SNPs) studied were significantly associated with longevity in humans (Nygaard et al 2013). The difference in our results and those of Nojima et al (2013) and Mercken et al (2013) could be due to different experimental organisms with greatly differing genetic architecture and/or due to specific effects of curcumin. Contrary to earlier findings of reduced CG9510 (Heinrichsen et al 2013) and AKHR (Iijima et al 2009) activity leading to increased triglyceride levels, flies from F C had significantly lower triglycerides (Fig.…”
Section: Discussioncontrasting
confidence: 68%
“…10A). However, other studies showed that loss of function in Akt prolonged lifespan in mice (Nojima et al 2013) and humans (Mercken et al 2013). Although Akt is known to play important roles in the signaling pathways of several cellular functions including nutrient metabolism, cell growth, apoptosis, and survival (Song et al 2005), none of the seven Akt1 single-nucleotide polymorphisms (SNPs) studied were significantly associated with longevity in humans (Nygaard et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in worms, flies, and mice consistently find that decreased signaling through the PI3K/Akt/mTORC1 signaling axis promotes longevity (Lamming, 2014), and calorie restriction, an intervention that promotes longevity in numerous species, decreases PI3K/Akt signaling in humans (Mercken et al ., 2013). …”
Section: Resultsmentioning
confidence: 99%
“…that resemble those of younger people, notably in inflammatory and nutrientsensing pathways 6 . Mice engineered to have reduced signalling in these pathways live longer; humans with similar mutations have lower rates of cancer and diabetes 2,7 .…”
Section: Treat Ageingmentioning
confidence: 99%